Characterization of liquid refrigerant R-123 flow emerging from a flooded evaporator tube bundle - Asher, William; Eckels, Steven J. (My University, 2018)
The distribution of liquid droplets emerging from an evaporator tube bundle is characterized for low-pressure refrigerant R-123 with a triangular tube arrangement of pitch 1.167. The purpose of this research is to improve understanding of the droplet ejection process to aid the design of evaporators typically used in larger chiller systems. A laser and camera system captured images of the evaporator headspace at varying conditions. Conventional shadowgraphy techniques were applied to recognize droplets and match droplets for velocity calculations. The evaporator conditions were varied with mass fluxes from 3.5 to 40.7 kg/s-m2 (2550 to 30000 lb/hr-ft2), top rows heat fluxes from 5.3 to 31.5 kW/m2 (1700 to 10000 Btu/hr-ft2), and outlet saturation temperatures of 4.4°C and 12.8°C (40°F and 55°F). Conditions ranged from flooded to dry-out on the top rows. Droplet number, size distribution, and velocity are presented. The experimentaly measured liquid volume fraction in the headspace is also presented. Liquid distribution in the headspace is found to be a strong function of all varied properties, particularly mass flux, liquid level, and saturation temperature. The high liquid-vapor density ratio of R-123 and corresponding high velocities make it particularly difficult to separate liquid droplets before they escape the tube bundle.
Citation: Asher, W., & Eckels, S. J. (2018). Characterization of liquid refrigerant R-123 flow emerging from a flooded evaporator tube bundle. Science and Technology for the Built Environment, 24(9), 1026–1038. https://doi.org/10.1080/23744731.2018.1464349